Water and ritual : the rise and fall of classic Maya rulers - Lucero, Lisa Joyce, 1962- (Linda Schele series in Maya and pre-Columbian studies., 2006)
In the southern Maya lowlands, rainfall provided the primary and, in some areas, the only source of water for people and crops. Classic Maya kings sponsored elaborate public rituals that affirmed their close ties to the supernatural world and their ability to intercede with deities and ancestors to ensure an adequate amount of rain, which was then stored to provide water during the four-to-five-month dry season. As long as the rains came, Maya kings supplied their subjects with water and exacted tribute in labor and goods in return. But when the rains failed at the end of the Classic period (AD 850-950), the Maya rulers lost both their claim to supernatural power and their temporal authority. Maya commoners continued to supplicate gods and ancestors for rain in household rituals, but they stopped paying tribute to rulers whom the gods had forsaken. In this paradigm-shifting book, Lisa Lucero investigates the central role of water and ritual in the rise, dominance, and fall of Classic Maya rulers. She documents commoner, elite, and royal ritual histories in the southern Maya lowlands from the Late Preclassic through the Terminal Classic periods to show how elites and rulers gained political power through the public replication and elaboration of household-level rituals. At the same time, Lucero demonstrates that political power rested equally on material conditions that the Maya rulers could only partially control. Offering a new, more nuanced understanding of these dual bases of power, Lucero makes a compelling case for spiritual and material factors intermingling in the development and demise of Maya political complexity.